Contrasting effects of habitat reduction, conversion and alteration on neutral and non neutral biological communities. Issue 7 (25th February 2014) - Teyssèdre, Anne; Robert, Alexandre
<x xml:space="preserve">Abstract</x> While habitat transformation driven by human activities is the main driver of current biodiversity changes, there is still no framework to explore and forecast the effects of different types of habitat changes on the richness and composition of biological communities. To tackle this issue, we modeled the dynamics of a regional meta‐community, composed either of ecologically equivalent species (neutral model) or of generalist and specialist species (specialization model), and explored the impact of the overall reduction, patch conversion or alteration of an original habitat into one or several other habitats of different total carrying capacity on the community metrics at equilibrium. Our simulations reveal strong interactions between the community model considered (neutral or specialization model) and the type of habitat change. Under neutrality, the impact of habitat changes on richness can be approached by a power law species–individual relationship (SIR), which may at constant density be simplified into the widely used power law species–area relationship (SAR), independent of the type of change. However, in the presence of generalist and specialist species, we found that 1) while habitat reduction in area also leads to approximately power law SIRs and SARs, 2) patch conversion and alteration have more complex effects on regional species richness, and 3) habitat alteration elicits the functional homogenization of communities, involving a decrease of their average level of specialization.